2019
DOI: 10.4049/jimmunol.1801221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TTP Phosphorylation in the Regulation of Inflammatory Cytokine Production by MK2/3

Abstract: Tristetraprolin (TTP) is an RNA-binding protein and an essential factor of posttranscriptional repression of cytokine biosynthesis in macrophages. Its activity is temporally inhibited by LPS-induced p38 MAPK /MAPKAPK2/3-mediated phosphorylation, leading to a rapid increase in cytokine expression. We compared TTP expression and cytokine production in mouse bone marrow-derived macrophages of different genotypes: wild type, MAPKAP kinase 2 (MK2) deletion (MK2 knockout [KO]), MK2/3 double deletion (MK2/3 double KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…We then asked whether the differences in TTP expression are accompanied by changes in phosphorylated (i.e., activated) MAPKAPK2 (MK2), a kinase known as important regulator of TTP expression. MK2 phosphorylates TTP at least on two residues (S52 and T178 in the mouse TTP) causing its stabilization and thereby increased expression ( 38 , 39 ). In agreement, MK2 was phosphorylated in BMDCs but not in BMDMs prior to LPS treatment ( Supplemental Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then asked whether the differences in TTP expression are accompanied by changes in phosphorylated (i.e., activated) MAPKAPK2 (MK2), a kinase known as important regulator of TTP expression. MK2 phosphorylates TTP at least on two residues (S52 and T178 in the mouse TTP) causing its stabilization and thereby increased expression ( 38 , 39 ). In agreement, MK2 was phosphorylated in BMDCs but not in BMDMs prior to LPS treatment ( Supplemental Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell type-specific post-translational modification of TTP may also contribute to the context-dependent function of TTP. Recent studies revealed that TTP contains a large number of phosphorylation sites with so far unexplained biological functions ( 39 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experimental data have confirmed that MAPK signal pathways are closely related to the regulation of anti-inflammatory cytokines, such as Bcl-6, TTP, and IL-10 (Pantoja-Escobar et al, 2019;Ronkina et al, 2019;Zhang et al, 2019) although there are still controversies with some showing an inhibitory effect of MAPKs on certain anti-inflammatory cytokines in BV2 cell line (Lee et al, 2015) and others having different opinions in bone marrow cells and microglial cells (Chi et al, 2006;Correa et al, 2010). In the kidney or renal cells, however, there is a lack of information on the relationship between MAPKs and anti-inflammatory cytokines in hypoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that TTP is phosphorylated at multiple sites by p38-regulated kinase MAPK-activated protein kinase 2 (MAPKAPK2) and that TTP activity is significantly affected by its phosphorylation status ( 32 34 ). TTP phosphorylation has been shown to result in reduced TTP activity/reduced binding of TTP to AREs, thus resulting in stabilization of its target mRNAs ( 35 ).…”
Section: Discussionmentioning
confidence: 99%